PENGARUH HARGA DAN E-SERVICE QUALITY TERHADAP BRAND SWITCHING DARI GRAB KE MAXIM PADA GENERASI Z DI KOTA KENDARI - Riska; Kumalasari, Fitri; Stiadi, Muhamad (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
The purpose of this research is to investigate how pricing affects generation Z's brand switching from Grab to Maxim in Kendari City, as well as how e-service quality affects this phenomenon. Data for this quantitative study was gathered via questionnaires, interviews, literature reviews, and observation. Purposive sampling was used to establish the study's sample size of 120 people, all of whom are members of Generation Z living in Kendari City. Validity and reliability tests are conducted on the research instrument using SPSS 30.0. By evaluating the measurement model (outer model) and the structural model (inner model) with smart pls 4.0, data analysis approaches utilizing structural equation modeling (SEM) based on partial least square (PLS) are employed. A p-value of 0.000 indicates that there is a positive and significant influence of the price variable on brand switching, according to the study's findings. Additionally, a p-value of 0.005 indicates that brand switching is positively and significantly impacted by the e-service quality variable.